The Relationship Between Workload, Shift Work, Work Shift, And Role Conflict On Work Stress In Idaman Regional Hospital Nurses Banjarbaru - Nur Qamaliah; Meitria Syahadatina Noor; Ihya Hazairin Noor; Mufatihatul Aziza Nisa; Ratna Setyaningrum (Lambung Mangkurat University, 2023)
The nursing profession has potential to experience stress in the workplace. Based on 2022, as many as 68% nurses at RSD Idaman Banjarbaru experience work stress. Apart from that, the Bed Turn Over value at RSD Idaman Banjarbaru exceeds the standard, namely 67,73. Based on Hurrell and McLaney’s theory, work stress can be impacted by numerous factors, one of which is the workload, work shift, and role conflict. The objective of this study is to examine the correlation involving workload, work shift and role conflict on work stress among nurses RSD Idaman Banjarbaru. The study employed a quantitative cross sectional design, with a research population comprising all 327 nurses at RSD Idaman Banjarbaru. The sample was 90 people using a proportional random sampling. The research instruments used the Nursing Stress Scale, the Nursalam workload questionnaire, and NIOSH questionnaire. The result of chi-square test show that there is a relationship between workload (p-value=0,022), role conflict (p-value=0,004), there is no relationship between work shifts (p-value=0,277) and work stress among nurses at RSD Idaman Banjarbaru. Based on the results, RSD Idaman Banjarbaru is expected to be able to evaluate the workload and adjust workload for each room, fulfilling resources and materials. It is also recommended that nurses be open with colleagues regarding problems in the workplace.